Serum folic acid: an effective indicator for arteriogenic erectile dysfunction - Feng, Xingliang; Mei, Yangyang; Xie, Pinpeng; Xing, Zhaoyu; Wang, Xiaogang; Cui, Li; Xu, Renfang (Frontiers in Endocrinology, 2023)
Abstract Background: The present study is the first study to explore the correlation between serum folic acid (FA) level and the penile arterial peak systolic velocity (PSV), measured by the penile color doppler ultrasonography (PDU) which could reflecting the endothelial function of penile artery directly. Materials and methods: A total of 244 consecutive ED patients and 72 healthy controls were included in our study from the Andrology department and healthy physical examination center respectively from June 2020 to April 2022. The serum FA was measured in ED patients and healthy controls, and the PDU examinations were conducted to all ED patients. The Pearson method was used to evaluate the correlation between FA level of PDU parameters in ED patients. The receiver operating characteristic (ROC) curve analysis is performed to calculate the sensitivity and specificity of related parameters for predicting Arteriogenic ED. Results: After the PDU examination, the serum FA level in patients diagnosed with arteriogenic ED was 8.08±2.64 ng/ml, lower than 10.78±2.87 ng/ml in healthy controls. There were no statistically significant differences in all basic parameters including age, body mass index (BMI), fasting blood glucose (FBG), total cholesterol (TC), and triglyceride (TG). Furthermore, we divided the arteriogenic ED into three subgroups according to the PSV range, as control group, non-vascular ED group, veno-occlusive ED group, and arterial ED group, to compare the serum FA level. The mean FA was 5.97±1.51ng/ml, and 8.21±2.37ng/ml, and 10.55±2.56ng/ml, in contrary to the PSV that was 15.75±2.39cm/s, 23.53±2.19cm/s, and 32.72±1.64cm/s. The positive correlation between PSV and FA level was found in arterigenic ED (r=0.605, P<0.001). Furthermore, when using the FA level with a cut-off value of 10.045 ng/ml to distinguishing the arteriogenic ED from healthy controls, the area under the curve (AUC) was 0.772 with the 95% confidential interval [0.696, 0.848] with the sensitivity of 0.611, and the specificity of 0.824. Conclusion: Serum FA level was positively related to the PSV in ED patients, and owned the ability to distinguish the arteriogenic ED from healthy controls. Taken together, the FA deficiency should be an independent risk factor for arteriegic ED.